(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper discusses engagement of non-governmental organisations and activist groups in environmental governance in Latvia. The research is based on desk research, a number of case studies and action research. Author attempts to analyse to what extent environmental NGOs and groups of activists have contributed to environmental governance and what role public participation plays in that. Author concludes that identification of problematic issues and policy planning are those stages where public participation and activism in environmental governance plays most crucial role. Contrary to common public believe about informal groups and environmental activism only attempting to oppose any proposed projects or new developments, these groups can and do play and important role in environmental governance. Author also concludes that institutional system that supports public participation is crucial in facilitating public involvement in environmental governance. Author also suggests that participatory environmental governance can better meet challenges of sustainability.